Effects of Lipoic Acid Supplementation on Activities of Cyclooxygenases and Levels of Prostaglandins E2 and F2α Metabolites, in the Offspring of Rats with Streptozotocin-Induced Diabetes - Hisham Y. Al-Matubsi; Ghaleb A. Oriquat; Mahmoud Abu-Samak; Othman A. Al Hanbali; Maher D. Salim (Journal of Diabetes Research)
Background. Our aim was to evaluate the protective effect of lipoic acid (LA) on fetal outcome of diabetic mothers. Methods. Diabetes was induced in female rats using streptozotocin and rats were made pregnant. Pregnant control (group 1; n=9; and group 2; n=7) or pregnant diabetic (group 3; n=10; and group 4; n=8) rats were treated daily with either LA (groups 2 and 4) or vehicle (groups 1 and 3) between gestational days 0 and 15. On day 15 of gestation, the fetuses, placentas, and membranes were dissected, examined morphologically, and then homogenized, to measure cyclooxygenase (COX) activities and metabolisms of prostaglandin (PG) E2 (PGEM) and PGF2α (PGFM) levels. The level of total glutathione was measured in the maternal liver and plasma and in all fetuses. Results. Supplementation of diabetic rats with LA was found to significantly (p<0.05) reduce resorption rates in diabetic rats and led to a significant (p<0.05) increase in liver, plasma, and fetuses total glutathione from LA-TD rats as compared to those from V-TD. Decreased levels of PGEM and elevated levels of PGFM in the fetuses, placentas, and membranes were characteristic of experimental diabetic gestation associated with malformation. The levels of PGEM in malformed fetuses from LA-TD mothers was significantly (p<0.05) higher than those in malformed fetuses from V-TD rats. Conclusions. LA treatment did not completely prevent the occurrence of malformations. Thus, other factors may be involved in the pathogenesis of the diabetes-induced congenital malformations.